Success of direct-acting antivirals for hepatitis C in HIV-positive patients in a tertiary hospital, Lima, Peru - Collins, Jaime A. (2024)
Objective: to present the results of the virological response in the medium term, based on the success of therapy with direct-acting antivirals (DAA) for chronic hepatitis C in the first series of HIVpositive patients reported at national level. Methods: longitudinal and prospective study from a series of HIV-positive patients with chronic hepatitis C treated with DAA and with evidence of success three years earlier. This was carried out between June and August 2023, at the Infectious Diseases Department of the EsSalud Guillermo Almenara Irigoyen National Hospital, Lima, Peru. The virological response of hepatitis C virus (HCV) was evaluated in terms of viral load. Results: of the nine patients included in the study, two were women (22%). One patient received sofosbuvir and daclatasvirseparately (SOF + DCV), while the remaining eight received sofosbuvir and velpatasvir in fixed-dose combination (SOF/ VEL). All patients maintained suppressed HIV viral load while, at 169 weeks, HCV viral load remained undetectable, except in one patient who presented an elevated viral load, which wasconsidered as a case of recurrent hepatitis C (11%). Conclusion: the results of the present series at 169 weeks are a sample of the benefits that can be obtained with DAAs for hepatitis C in the potential eradication of the disease.